2004
DOI: 10.1097/01.shk.0000131192.02909.4c
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxic Ventilation Reduces Six-Hour Mortality After Partial Fluid Resuscitation From Hemorrhagic Shock

Abstract: Ventilation with 100% oxygen (Fio(2) 1.0; hyperoxic ventilation; HV) as an alternative to red blood cell transfusion enables survival in otherwise lethal normovolemic anemia. The aim of the present study was to investigate whether HV as a supplement to fluid infusion therapy could also restore adequate tissue oxygenation and prevent death in otherwise lethal hemorrhagic shock. In 14 anesthetized pigs ventilated on room air (Fio(2) 0.21), hemorrhagic shock was induced by controlled withdrawal of blood (target m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Bigdeli MR et al report that normobaric hyperoxia can produce free radical oxygen to prevent ischemic brain injury [24]. Recently, it was reported that 100% oxygen ventilation is beneficial to animal models with systemic inflammatory response syndrome (SIRS)/shock/sepsis [4,5]. Our previous study showed that 100% oxygen inhalation for 2 or 3 h starting at 4 and 12 h after zymosan injection, respectively, can prevent abnormal changes of serum biochemical parameters, improve tissue oxygenation, organ pathologic changes, and 14-d survival rate, while 100% oxygen inhalation for 1 or 4 h starting at the same time as zymosan injection has little protective effects [2].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Bigdeli MR et al report that normobaric hyperoxia can produce free radical oxygen to prevent ischemic brain injury [24]. Recently, it was reported that 100% oxygen ventilation is beneficial to animal models with systemic inflammatory response syndrome (SIRS)/shock/sepsis [4,5]. Our previous study showed that 100% oxygen inhalation for 2 or 3 h starting at 4 and 12 h after zymosan injection, respectively, can prevent abnormal changes of serum biochemical parameters, improve tissue oxygenation, organ pathologic changes, and 14-d survival rate, while 100% oxygen inhalation for 1 or 4 h starting at the same time as zymosan injection has little protective effects [2].…”
Section: Discussionmentioning
confidence: 98%
“…Some evidence shows that improving tissue oxygenation is considered as the key mechanism of the protective effects by hyperoxia [2,4,5], whereas our recent article showed that ROS scavenger pretreatment partly abolishes the protective action of 100% oxygen treatment against zymosan-induced generalized inflammation in mice [2], suggesting that there may be multiple mechanisms underlying the protective effect of hyperoxia including the important role of ROS. These results are similar to other study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, hyperoxia has benefits: Oxygen has antibiotic activity (6), and, in fact, perioperative hyperoxia reduced wound infections after abdominal surgery (7,8). Furthermore, ventilation with 100% oxygen improved survival in various shock models characterized by depressed oxygen delivery (9,10). In rats undergoing ischemia/reperfusion and hemorrhage, hyperoxia increased blood pressure, redistributed cardiac output to the hepatosplanchnic organs and the kidney, improved microcirculatory perfusion, and reduced the systemic inflammatory response (11,12).…”
mentioning
confidence: 98%
“…As an alternative to the immediate transfusion of red blood cells, "rescue therapy" with hyperoxic ventilation (HV, ventilation with pure oxygen, FIO 2 1.0) has already been demonstrated effective in reducing the mortality rate of critical anemic (7,8) and hypoxemic hypoxia (i.e., lethal methemoglobinemia) (9). The particular impact of "prophylactic" HV (i.e., initiation of HV during the emergence of dilutional anemia) on anemia tolerance and in particular the impact of HV on the dimension of Hb crit is still unknown.…”
mentioning
confidence: 99%